2023
DOI: 10.1021/acs.jafc.3c07379
|View full text |Cite
|
Sign up to set email alerts
|

Efficient De Novo Biosynthesis of Curcumin in Escherichia coli by Optimizing Pathway Modules and Increasing the Malonyl-CoA Supply

Jianbin Chen,
Weigao Wang,
Lian Wang
et al.

Abstract: Curcumin is a natural phenylpropanoid compound with various biological activities and is widely used in food and pharmaceuticals. A de novo curcumin biosynthetic pathway was constructed in Escherichia coli BL21(DE3). Optimization of the curcumin biosynthesis module achieved a curcumin titer of 26.8 ± 0.6 mg/L. Regulating the metabolic fluxes of the β-oxidation pathway and fatty acid elongation cycle and blocking the endogenous malonyl-CoA consumption pathway increased the titer to 113.6 ± 7.1 mg/L. Knockout of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…The final coniferyl alcohol production in the resultant strain was noted to be much higher than the previously reported levels. , Heterologous expression of srpB alleviated the toxicity of ferulic acid and promote the biosynthesis of curcumin in E. coli . It has been reported that a HucR-based dynamic regulation system can be combined to control metabolic flux to reduce excessive accumulation of ferulic acid .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The final coniferyl alcohol production in the resultant strain was noted to be much higher than the previously reported levels. , Heterologous expression of srpB alleviated the toxicity of ferulic acid and promote the biosynthesis of curcumin in E. coli . It has been reported that a HucR-based dynamic regulation system can be combined to control metabolic flux to reduce excessive accumulation of ferulic acid .…”
Section: Discussionmentioning
confidence: 86%
“…SrpB was also used to alleviate the effect of ferulic acid on the biosynthesis of curcumin in E. coli, resulting in an increase in curcumin production from 113.6 to 137.5 mg/L . Overexpression of ompF (encoding outer membrane pore protein) has been reported to significantly enhance the biosynthesis of polyphenol resveratrol in E.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to our study, de novo curcumin biosynthesis had only been achieved in genetically modified E. coli. , …”
Section: Resultsmentioning
confidence: 99%
“…However, curcumin has only been synthesized from simple carbon sources in genetically modified E. coli . 12 , 21 E. coli is not a Generally Regarded As Safe (GRAS) organism, and the expression of the heterologous genes usually relies on the use of plasmids, which require constant selective antibiotic pressure for maintaining, and the supplementation of expensive inductors, which is also not desirable. The yeast S. cerevisiae is a role model microorganism for genetic engineering purposes due to its safety status and clear metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%